History from the Selangor Journal, 1892-1897 - Gullick, J.M (MBRAS reprint, 2007)
In editing the 'Selangor Journal', John Russell, the government printer, obtained contributions from many sources, and published it fortnightly instalments over five years from 1892 to 1897. It served as a local newsletter until replaced in 1896 by the Malay Mail daily newspaper. The Journal was both a chronicle of the times and a means of publishing reports of events and people, past and present, the endures as material of much historical value. The purpose of this reprint of selected passages is to offer to the modern reader convenient access to a publication copies of which are difficult to find, and a means of tracing material on specific topics that is scattered through the original 2000 odd pages of the Journal.